2017
DOI: 10.1038/cdd.2017.51
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells sense mitochondria released from damaged cells as danger signals to activate their rescue properties

Abstract: Mesenchymal stem cells (MSCs) protect tissues against cell death induced by ischemia/reperfusion insults. This therapeutic effect seems to be controlled by physiological cues released by the local microenvironment following injury. Recent lines of evidence indicate that MSC can communicate with their microenvironment through bidirectional exchanges of mitochondria. In particular, in vitro and in vivo studies report that MSCs rescue injured cells through delivery of their own mitochondria. However, the role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
227
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(232 citation statements)
references
References 56 publications
3
227
1
1
Order By: Relevance
“…38 In particular, the mitochondria transfer between differentiated and mesenchymal stem cells was observed in cardiomyocytes and endothelial cells as a means to rescue injured tissues. 39 Similarly, mitochondria are able to be internalized by different types of cells, by macro pinocytosis which is an endocytic pathway specific for large vesicles. 40 Clinical transplantation of mitochondria between cells is an active area of research but the specific mechanisms and critical factors involved in natural mitochondria transfer between the donor cells and recipient cells remain to be fully characterized.…”
Section: Discussionmentioning
confidence: 99%
“…38 In particular, the mitochondria transfer between differentiated and mesenchymal stem cells was observed in cardiomyocytes and endothelial cells as a means to rescue injured tissues. 39 Similarly, mitochondria are able to be internalized by different types of cells, by macro pinocytosis which is an endocytic pathway specific for large vesicles. 40 Clinical transplantation of mitochondria between cells is an active area of research but the specific mechanisms and critical factors involved in natural mitochondria transfer between the donor cells and recipient cells remain to be fully characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial transfer of hiPS‐MSCs effectively protects corneal epithelial cells from mitochondrial damage . Rodriguez and coworkers demonstrated that MSCs can sense mitochondria released from damaged cells as danger signals to activate their rescue properties, thus acting as both sensors and rescuers of the tissue injury .…”
Section: Therapeutic Effects Of Ps‐mscs In Vivomentioning
confidence: 99%
“…Beside increased mitophagy, MSCs have adopted a particular strategy to accomplish this goal, i.e., they outsource mitophagy to bystander macrophages in the niche, at the same time delivering miRNA to inhibit macrophage activation that may occur since mitochondria may trigger a pattern recognition receptor reactivity [115]. On the other hand, MSCs may sense mitochondria released from damaged somatic cells as a signal to increase their modulatory activity [116].…”
Section: In Vivo Msc Senescencementioning
confidence: 99%